2014
DOI: 10.1093/nar/gku468
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of nucleic acid binding byNicotiana tabacumglycine-rich RNA-binding protein: implications for its RNA chaperone function

Abstract: Glycine-rich RNA-binding proteins (GR-RBPs) are involved in cold shock response of plants as RNA chaperones facilitating mRNA transport, splicing and translation. GR-RBPs are bipartite proteins containing a RNA recognition motif (RRM) followed by a glycine-rich region. Here, we studied the structural basis of nucleic acid binding of full-length Nicotiana tabacum GR-RBP1. NMR studies of NtGR-RBP1 show that the glycine-rich domain, while intrinsically disordered, is responsible for mediating self-association by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 51 publications
7
24
0
Order By: Relevance
“…Deletion of AtGR-RBP7 leads to low-temperature sensitive phenotypes, highlighting its role in optimal plant adjustment to cold stress [245]. NMR analysis confirms the structural disorder of the GR domain for NtGR-RBP1, an AtGR-RBP7 orthologue from Nicotiana tabacum [246]. As expected, NtGR-RBP1 is shown to bind RNA and single stranded DNA through the RRM.…”
Section: Glycine Rich-rna Binding Proteins (Gr-rbps)supporting
confidence: 66%
See 1 more Smart Citation
“…Deletion of AtGR-RBP7 leads to low-temperature sensitive phenotypes, highlighting its role in optimal plant adjustment to cold stress [245]. NMR analysis confirms the structural disorder of the GR domain for NtGR-RBP1, an AtGR-RBP7 orthologue from Nicotiana tabacum [246]. As expected, NtGR-RBP1 is shown to bind RNA and single stranded DNA through the RRM.…”
Section: Glycine Rich-rna Binding Proteins (Gr-rbps)supporting
confidence: 66%
“…Furthermore, the NtGR-RBP1 GR interacts transiently with its RRM domain, promoting self-association to effectively increase its local concentration and hence its affinity for nucleic acids. These findings suggest a mechanism for the unfolding of nonnative structures in RNA by NtGR-RBP1, which may be involved in enhancing its RNA chaperone activity [246].…”
Section: Glycine Rich-rna Binding Proteins (Gr-rbps)mentioning
confidence: 81%
“…The interaction between ORRM4 and ORRM3 was shown to be mediated by the C-terminal GR domain of ORRM4. NMR studies of NtGR-RBP1, which contains an N-terminal RRM domain and a C-terminal GR domain like ORRM4, show that the GR domain is responsible for mediating self-association by transient interactions with its RRM domain (NtRRM; Khan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…While the structural architectures of several eukaryotic RRM-containing proteins have been reported, 20 22 our structural and functional understanding of plant RRM and plant glycine-rich RNA-binding proteins is less well developed. To this date, the three-dimensional (3D) structures of only two plant-derived GR-RBPs have been reported, 23 , 24 and none from barley. The present work is the first structural report of a barley GR-RBP protein.…”
mentioning
confidence: 99%
“…Moreover, protein–protein interactions were detected using NMR chemical shift perturbation experiments between the RRM and GR domains of Hv GR-RBP1, suggesting that at least in vitro , these two domains self-associate, results that are consistent with what has been observed for the Nicotiana tabacum Nt GR-RBP1 protein. 24 Nucleic acid interaction assays indicated that the GR domain of Hv GR-RBP1 can bind to single-stranded RNA (ssRNA) in the absence of the RRM domain. As anticipated based on the Hv GR-RBP1 sequence similarity to the Nicotiana tabacum Nt GR-RBP1 protein and a recent report by Khan et al, 24 1 H/ 15 N chemical shift perturbation experiments established that the N-terminal RRM domain of Hv GR-RBP1 can bind, albeit weakly, to a 6-nucleotide single-stranded DNA fragment containing the consensus sequence 5′-TTCTGX-3′, a DNA equivalent of the 5′-UUCUGA-3′ RNA sequence previously identified as a key nucleotide binding motif for the Arabidopsis protein At GRP7.…”
mentioning
confidence: 99%